INTERACTIVE TEACHING METHODS AS A MEANS OF ACTIVATING THE COGNITIVE ACTIVITY OF STUDENTS - Hulai , Olha; Moroz , Iryna; Shemet , Vasylyna; Shevchuk , Mykola (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article analyzes interactive learning as a modern pedagogical technology. The main strengths and weaknesses of the application of this approach are highlighted. Specific interactive methods of teaching chemistry are considered, where students have a choice of actions and can take the initiative. The use of interactive methods allows not only to deepen subject knowledge and skills, but also to develop communication skills and solve problems in a team.